Therapeutic potential of niobium- or gallium-doped bioactive glasses for treatment of bone disorders : an in vitro and in vivo experimental study = Potencial terapêutico de vidros bioativos contendo nióbio ou gálio no tratamento de desordens ósseas: estudo experimental in vitro e in vivo - Souza, Lucas Pereira Lopes de, 1989- (2018)
Orientador: José Angelo Camilli